Asesmen Kompetensi Pedagogik Calon Guru: Studi Kasus pada Mahasiswa Program Studi PGSD - Kuntarto, Eko; Maryono, Maryono (STKIP PGRI Bandar Lampung, 2020)
This study aims to assess the pedagogical competence of student teacher candidates. This research is a case study. The research object is pedagogic competence. The research subjects were 200 PGSD students at Jambi University who were selected randomly. The research instrument used the Teacher Competency Assessment application. All data is retrieved online. Data analysis was performed by classification based on ideal mean score and ideal standard deviation, and non-parametric analysis using Kruskal-Wallis difference test and Spearman correlation test. The results showed (1) the mastery of the characteristics of the third semester students was 68.33, the fifth semester was 80.83m and the seventh semester was 82.50; (2) Mastery of learning theory and teaching learning principles in the three groups of students, respectively 71.50, 81.25, and 82.50; (3) ability to develop curriculum, respectively 63.50, 82.50, and 81.25; (4) The ability to carry out educational learning activities, respectively 55.90, 84.54, and 83.72; (5) there is a significant relationship between student teacher candidates pursued and pedagogical competence.